Attention to woman in case of induced abortion: the perception of professional nursing - Eveline Franco da Silva; Dinifer Concatto Trevisan; Elisiane Lorenzini; Ana Carla Fischer Pruss; Márcia Rejane Strapasson; Ana Lucia de Lourenzi Bonilha (Universidade Federal de Santa Maria, 2015)
Aim: to know the perception of nurses toward to the assistance to women in induced abortion process. Method: descriptive, qualitative study with 12 nursing professionals from the obstetric center of a public hospital in Southern of Brazil. The data, originated from semi-structured interviews, were analyzed based in thematic analysis. The study was approved by the Ethics Committee. Results: two categories emerged: the role of nursing in care for women in induced abortion process; and not being able to care for women in induced abortion process. Conclusion: the interviewed professionals did not feel qualified to assist and realized that they cared mechanically. We need to equip professionals through training to develop specific skills and knowledge about the humane treatment of women in this condition